2017
DOI: 10.4102/curationis.v40i1.1784
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of burnout, compassion fatigue and compassion satisfaction in undergraduate nursing students at a tertiary education institution in KwaZulu-Natal

Abstract: BackgroundStudies have investigated burnout and compassion fatigue among nurses and effects in the nursing profession. However, there are limited investigations of burnout and compassion fatigue among undergraduate nursing students in South Africa, as nursing students may experience distressful situations during their nursing education course, which may have an impact during their training and in their profession as they graduate.PurposeThe purpose of this descriptive study was to describe compassion satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…Equal numbers of participants reported low or high emotional exhaustion (39.6 and 39.6%, respectively). Overall, 46.1% reported high, 33.8% moderate, and 20% low burnout.There were significant associations between the psychological health subscale of the World Health Organization Quality of Life Assessment and all subscales of the MBI, in particular emotional exhaustion ( p < 0.01). Gordon, 2016 [117]South AfricaOral hygiene students ( N = 89)MBIEmotional exhaustion (mean ± SD): 3.3 ± 1.8Depersonalization: 1.3 ± 1.6Personal accomplishment: 3.7 ± 1.7There were significant differences in burnout between 1st, 2nd, and 3rd year students ( p = 0.039). Mason, 2012 [118]South AfricaNursing students ( N = 80)ProQOL, burnout subscale63.75% had a moderate to high risk for burnoutBurnout was significantly associated with compassion fatigue and negatively associated with compassion satisfaction ( p < 0.01). Mathias, 2017 [119]South AfricaUndergraduate nursing students ( N = 67)ProQOL, burnout subscale6% had low levels of burnout, 94% moderate, & none had high burnoutThe majority of nursing students experienced average levels of burnout, compassion fatigue, and compassion satisfaction. Njim, 2018 [120]CameroonNursing students ( N = 447)Oldenburg Burnout InventoryDisengagement (mean ± SD): 17.1 ± 3.1Exhaustion: 20.9 ± 3.0Satisfaction with results and regret with choice of nursing studies were determinants of burnout ( p < 0.05) Njim, 2019 [121]CameroonMedical students ( N = 413)Oldenburg Burnout InventoryDisengagement (mean ± SD): 16.6 ± 3.4Exhaustion: 20.5 ± 3.5Marital status, relationship difficulties, cumulative GPA, regretting the choice of medical studies, and recreational drug use significantly predicted burnout ( p < 0.05). Stein, 2016 [122]South AfricaParamedic students ( N = 93)CBIWork related burnout (mean ± SD): 49.1 ± 12.9Personal burnout: 53.4 ± 15.0Patient care related burnout: 34.0 ± 19.5Overall burnout: 45.2 ± 11.531% reported high burnoutThere were no significant differences in mean burnout between the 4 academic years of study in work-related, personal, and patient care-related burnout. Abbreviations : CBI Copenhagen Burnout Inventory, MBI Maslach Burnout Inventory, MBI-HSS Maslach Burnout Inventory - Human Services Survey, ProQOL Professional Quality of Life Scale…”
Section: Methodsmentioning
confidence: 99%
“…Equal numbers of participants reported low or high emotional exhaustion (39.6 and 39.6%, respectively). Overall, 46.1% reported high, 33.8% moderate, and 20% low burnout.There were significant associations between the psychological health subscale of the World Health Organization Quality of Life Assessment and all subscales of the MBI, in particular emotional exhaustion ( p < 0.01). Gordon, 2016 [117]South AfricaOral hygiene students ( N = 89)MBIEmotional exhaustion (mean ± SD): 3.3 ± 1.8Depersonalization: 1.3 ± 1.6Personal accomplishment: 3.7 ± 1.7There were significant differences in burnout between 1st, 2nd, and 3rd year students ( p = 0.039). Mason, 2012 [118]South AfricaNursing students ( N = 80)ProQOL, burnout subscale63.75% had a moderate to high risk for burnoutBurnout was significantly associated with compassion fatigue and negatively associated with compassion satisfaction ( p < 0.01). Mathias, 2017 [119]South AfricaUndergraduate nursing students ( N = 67)ProQOL, burnout subscale6% had low levels of burnout, 94% moderate, & none had high burnoutThe majority of nursing students experienced average levels of burnout, compassion fatigue, and compassion satisfaction. Njim, 2018 [120]CameroonNursing students ( N = 447)Oldenburg Burnout InventoryDisengagement (mean ± SD): 17.1 ± 3.1Exhaustion: 20.9 ± 3.0Satisfaction with results and regret with choice of nursing studies were determinants of burnout ( p < 0.05) Njim, 2019 [121]CameroonMedical students ( N = 413)Oldenburg Burnout InventoryDisengagement (mean ± SD): 16.6 ± 3.4Exhaustion: 20.5 ± 3.5Marital status, relationship difficulties, cumulative GPA, regretting the choice of medical studies, and recreational drug use significantly predicted burnout ( p < 0.05). Stein, 2016 [122]South AfricaParamedic students ( N = 93)CBIWork related burnout (mean ± SD): 49.1 ± 12.9Personal burnout: 53.4 ± 15.0Patient care related burnout: 34.0 ± 19.5Overall burnout: 45.2 ± 11.531% reported high burnoutThere were no significant differences in mean burnout between the 4 academic years of study in work-related, personal, and patient care-related burnout. Abbreviations : CBI Copenhagen Burnout Inventory, MBI Maslach Burnout Inventory, MBI-HSS Maslach Burnout Inventory - Human Services Survey, ProQOL Professional Quality of Life Scale…”
Section: Methodsmentioning
confidence: 99%
“…Compassion fatigued nurses would exhibit apathy, depression, errors in clinical judgement, sleep disorders, hypertension, feeling of impotence, irritation and emotional suppression, and even poor quality of work, being determinant in patient safety and quality of care and compromising a compassionate care [13,15]. High levels of compassion fatigue have recently been reported in several nursing specialties, such as emergency nurses [16,17], heart and vascular nurses [18], oncology nurses [19,20], midwives [21], critical care nurses [22], or pediatric nurses [23], and in samples from different countries, including Australia [24,25], Canada [26], Ireland [27], South Africa [28], the UK [29], or the US [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Cross-Sectional/Cohort Study Medical students Taiwan ( n = 127) Contributors to burnout included: Male gender; younger age; poor self-esteem; and decreased sense of control Mason ( 2018 ) Cross-Sectional Study Nursing students South Africa ( n = 150) Attributes & Consequences : CF and burnout are closely related to pessimistic existential attitudes; optimism is predictive of CS Mason and Nel ( 2012 ). Prevalence Study Nursing students South Africa ( n = 80) −63.75% of total sample presented with moderate to high risk for burnout Attributes : High scores of burnout occurred during final year of program Mathias and Wentzel ( 2017 ). Prevalence Study Nursing students in 3rd & 4th years of study South Africa ( n = 67) −94% of sample presented with moderate risk for burnout −95.5% reported average levels of compassion satisfaction McArthur et al ( 2017 ).…”
Section: Search Results and Appraisalmentioning
confidence: 99%
“…Five studies in the final review focussed on CF among undergraduate nursing students. In South Africa, two prevalence studies were conducted (Mason and Nel 2012 ; Mathias and Wentzel 2017 ), however, analysis did not include any predictor or independent variables. Regression analysis conducted by Mason ( 2018 ) found that among South African nursing students, those with pessimistic attitudes were more likely to experience CF.…”
Section: Search Results and Appraisalmentioning
confidence: 99%